Architecture a visual history - Glancey, Jonathan (Dorling Kindersley Limited, 2017)
Architecture tells the story of the world's most incredible buildings, from the ancient world to the present day. Now fully updated, this stunning new edition covers contemporary architecture and green buildings, with incredible new photography to transport you to the most interesting and iconic buildings on earth.